Sowing Date Effects on Growth, Flowering, Oil Content and Seed Yield of Canola Cultivars - Uzun, Bulent; Zengin, Omran; Furat, Seymus; Akdesir, Ozgur (Asian Journal of Chemistry, 2010)
A comprehensive analysis of response to sowing date in canola has been studied under true Mediterranean type environment. The field research were conducted to investigate the influence of sowing dates on growth and flowering patterns and seed yield of canola cultivars during 2004-05 and 2005-06 growing seasons. Six sowing dates were established at about 20 days intervals from 1st October to 10th January. The responses of growth, flowering, oil content, seed yield and components of yield were consistent in both years. Cultivars tended to respond similarly to sowing date for the characters studied. The results apparently showed that late sowings caused to decline in seed yield of canola cultivars. The decline of seed yield with delay in sowing date could be explained by shortening the length of the reproductive period and consequently the potential grain-filling period. Practically, later planted plants reached both pre-flowering and post-flowering period sooner compared to those planted earlier. The present study highlights the practical importance of sowing date in growing and flowering patterns, yield formation and oil content of canola cultivars.